Some Empirical Evidence on the Quantity Theoretic Proposition of Money in ASEAN-5 - Puah, Chin-Hong; Muzafar Shah, Habibullah; Shazali, Abu Mansor (Universiti Malaysia Sarawak, (UNIMAS), 2008)
This study examines the international evidence on long-run neutrality (LRN) of money based on low frequency data from five emerging ASEAN economies, namely, Indonesia, Malaysia, the Philippines, Singapore, and Thailand, using a nonstructural reduced-form bivariate ARIMA model proposed by Fisher and Seater (1993). Empirical evidence shows that the This study examines the international evidence on long-run neutrality (LRN) of money based on low frequency data from five emerging ASEAN economies, namely, Indonesia, Malaysia, the Philippines, Singapore, and Thailand, using a nonstructural reduced-form bivariate ARIMA model proposed by Fisher and Seater (1993). Empirical evidence shows that the classical proposition cannot be rejected with respect to real export except for Thailand. However, the LRN test results are not robust to changes in money supply in countries under study with respect to real output. The narrow monetary aggregate seems to have greater impact on Indonesia, Malaysia, and Thailand economic activities as compared to the other two countries.classical proposition cannot be rejected with respect to real export except for Thailand. However, the LRN test results are not robust to changes in money supply in countries under study with respect to real output. The narrow monetary aggregate seems to have greater impact on Indonesia, Malaysia, and Thailand economic activities as compared to the other two countries.